Fakultas Pertanian Universitas Muhammadiyah Purwokerto - Bambang Nugroho; Aman Suyadi (Universitas Muhammadiyah Purwokerto, 2013)
This research aimed to see the first appearance progeni (local S1) Selfing cultivar maize of Srowot Banyumas. It was taken place in Environment of Agricultural Faculty, University of Muhammadiyah Purwokerto with height more or less 85 m dpl. This research was conducted less than 6 month by using Complete Random Device (RAL). Trial factor are Varietas ( V) and Pollination by itself/selfing (S). Varietas Factor consisted of by 1 type: V1 = local Varietas Maize of Srowot Banyumas with 9 Parental. Selfing Factor consisted of 2 factors: S0 = Is not conducted by selfing (pollination by itself), S1 = conducted by selfing (pollination by itself). These factors obtained by 18 combination, and each factor using 3 restating. The result showed that there is inbreeding depression to component vegetative growth crop, in the form of high degradation of crop equal to 63,19 cm (31,28 %), and degradation sum up the leaf 2,72 piece of (22,67 %) effect of treatment selfing. Inbreeing depression that occured to result component only seen at seed weight per cob that there is weight degradation about 14,47 g or 23,51 % effect of treatment selfing Key words: first progeni performance (S1), selfing, local cultivar maize of srowot Banyumas